STRATEGI KEBERHASILAN PERUBAHAN KURIKULUM PONDOK PESANTREN MU’ADALAH BAITUL ARQOM BALUNG JEMBER - Nursyamsiyah, Siti; Huda, Hairul (MPI STAI Sangatta Kutai Timur, 2023)
The curriculum is the foundation for measuring the success of learning. The process of changing the curriculum follows the development of the times and the needs of society. Leaders as leading sectors as determinants of curriculum change and are supported by educators and education staff. This study uses a qualitative approach and a type of field research. Data was obtained through observation, interviews, and documentation. The data analysis technique uses triangulation. The results showed that there were four successful strategies for changing the Baitul Arqom Islamic boarding school curriculum, namely: 1) preparing effective leadership to encourage change; 2) creating a curriculum capable of changing high priorities; 3) planning resources for effective curriculum changes; and 4) ensure all students participate.